A novel oral prodrug-targeting transporter MCT 1: 5-fluorouracil-dicarboxylate monoester conjugates - Yixin Sun; Dongyang Zhao; Gang Wang; Qikun Jiang; Mengran Guo; Qiming Kan; Zhonggui He; Jin Sun (Elsevier, 2019)
Monocarboxylate transporter 1 (MCT1) is responsible for oral absorption of short-chain monocarboxylic acids from small intestine, hence, it's likely to serve as an ideal design target for the development of oral prodrugs. However, potential application of MCT1 to facilitate the oral delivery is still unclear. Irregular oral absorption, poor permeability and bioavailability greatly limit the oral delivery efficiency of 5-fluorouracil (5-FU). Herein, we design three 5-FU-fatty acid conjugates targeting intestinal MCT1 with different lipophilic linkages. Interestingly, due to high MCT1 affinity and good gastrointestinal stability, 5-FU-octanedioic acid monoester prodrug exhibited significant improvement in membrane permeability (13.1-fold) and oral bioavailability (4.1-fold) compared to 5-FU. More surprisingly, stability experiment in intestinal homogenates showed that 5-FU prodrugs could be properly activated to release 5-FU within intestinal cells, which provides an ideal foundation for the improvement of oral bioavailability. In summary, good gastrointestinal stability, high membrane permeability and appropriate intestinal cell bioactivation are the important factors for high-efficiency 5-FU oral prodrugs, and such work provides a good platform for the development of novel oral prodrugs targeting intestinal transporters. Keywords: 5-Fluorouracil, Prodrugs, Monocarboxylate transporter 1, Permeability, Oral bioavailability